The effects of combination-therapy of tocilizumab and baricitinib on the management of severe COVID-19 cases: a randomized open-label clinical trial - Dastan, Farzaneh; Jamaati, Hamidreza; Barati, Saghar; Varmazyar, Shahrzad; Yousefian, Sahar; Niknami, Elmira; Tabarsi, Payam (Frontiers in Pharmacology, 2023)
Background: Tocilizumab and baricitinib are considered standard treatments for hospitalized COVID-19 patients with an inflammatory status. However, the effects of co-administering these medications aiming for more rapid patient recovery are controversial among practitioners. The potential benefits include the rapid improvement of patients and regulation of the immune system, and the potential risks include the increased chance of serious adverse events, including infections. This study aimed to investigate the effects of co-administering these two medications on the 28-day mortality rate, other efficacy parameters, and safety issues. Methods: In this randomized open-label trial, 68 patients were recruited. The study was conducted at Dr. Masih Daneshvari Hospital during 6 months (from 21 March 2022 to 23 August 2022). Severely ill patients aged between 18 and 100 years old with confirmed COVID-19 were enrolled. The primary outcomes included the need for invasive mechanical ventilation and a 28-day mortality rate. Secondary outcomes included the need for non-invasive mechanical ventilation, the need for admission to the intensive care unit (ICU), the length of hospital stay, and the need for a second dose of tocilizumab. Safety assessments were also performed for 28 days. The data were collected from the patients’ medical records, which included age, gender, and comorbidities. Results: The 28-day mortality rate or the need for mechanical ventilation was not statistically different among the two groups (p-value = 0.49 for both outcomes). The need for non-invasive mechanical ventilation, the need for admission to the ICU, or the need for a second dose of tocilizumab and the length of hospital stay was not affected either (p-value = 1; 0.1; 0.49 and 0.9, respectively). One patient developed thrombosis in the combination group. No adverse events related to infectious complications were recorded in any groups. Conclusion: This study showed no beneficial effects of combining tocilizumab and baricitinib in managing severe COVID-19 cases. However, the need for ICU admission was meaningfully lower in the combination group. Studies with larger sample sizes are needed to confirm these results. Clinical Trial Registration: Identifier: RCT20151227025726N30M